2011
DOI: 10.1136/bmj.c7085
|View full text |Cite
|
Sign up to set email alerts
|

Going local: devolving national pay for performance programmes

Abstract: The recommendation that part of the Quality and Outcomes Framework be devolved to local areas has not been widely implemented. However, the experience of Christopher Millett and colleagues shows that it can help focus attention on local health needs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…As some studies have suggested that the differential effect of QOF by practices' with different baseline performance, particularly the worst performers improved at the fastest rate after QOF [14], [15]. For this analysis, we created 3 approximately equal-sized number of GP practices groups based on their baseline performance in year 2003 for each indicator.…”
Section: Methodsmentioning
confidence: 99%
“…As some studies have suggested that the differential effect of QOF by practices' with different baseline performance, particularly the worst performers improved at the fastest rate after QOF [14], [15]. For this analysis, we created 3 approximately equal-sized number of GP practices groups based on their baseline performance in year 2003 for each indicator.…”
Section: Methodsmentioning
confidence: 99%
“…12 The QOF Plus Health Check differs from the national minimum Health Check by including patients with hypertension and CKD. In the first year of the programme, patients determined to have high CVD risk (greater than 20 percent risk using a designated risk score) from existing medical records were prioritized for screening.…”
Section: Methodsmentioning
confidence: 99%
“…NHS Health Check was implemented ahead of the national schedule, beginning in July 2008 and organized under a local incentive framework for general practice (QOF Plus) (Box 1). 10 The primary care trust provided guidance and training 15 on implementation of the NHS Health Check programme to 31 independent general practices in the area; the programme was then largely administered by nurses and health care assistants employed by the practices.…”
Section: Nhs Health Check In Hammersmith and Fulham Londonmentioning
confidence: 99%
“…A small number of areas include Health Checks within a local quality outcomes framework (QOF), a more complex pay-forperformance framework. 10 We aimed to assess the impact of a local financial incentive scheme on uptake and statin prescribing in the first 2 years of Health Checks. Given inequalities in CVD risk factors, including smoking and obesity, 11,12 and total CVD burden, 13 we also examined whether uptake and prescribing within the programme differed between socio-demographic groups.…”
Section: Introductionmentioning
confidence: 99%